Narrative review: Risk of eating disorders and nutritional deficiencies with dietary therapies for irritable bowel syndrome. Issue 1 (13th July 2021) - Simons, Madison; Taft, Tiffany H.; Doerfler, Bethany; Ruddy, Johannah S.; Bollipo, Steven; Nightingale, Scott; Siau, Keith; van Tilburg, Miranda A. L.
Abstract: Background and Aims: Dietary treatments are growing in popularity as interventions for chronic digestive conditions. Patients with irritable bowel syndrome (IBS) often change their eating behaviors to mitigate symptoms. This can occur under the direction of their physician, a dietitian, or be self‐directed. Poorly implemented and monitored diet treatments occur frequently with considerable risks for negative consequences. We aim to review the literature related to dietary treatments and risks associated with nutritional deficiencies and disordered eating. Methods: Searches were conducted from June to December 2020 on PubMed, MEDLINE, EMBASE, DARE and the Cochrane Database of Systematic Reviews using relevant keywords based on the Patient, Intervention, Comparator and Outcome (PICO) format. Studies included both adult and pediatric populations. Results are synthesized into a narrative review. Results: While dietary approaches are efficacious in many research studies, their translation to clinical practice has been less clear. Patients with IBS are at risk for nutritional deficiencies, disordered eating, increased anxiety, and decreases in quality of life in both adult and pediatric groups. Conclusions: Physicians prescribing dietary treatment for IBS should be aware of nutritional and psychological risks and implement mitigation measures. These include using a combination of brief, validated questionnaires and clinical history, and collaboration with registered dietitians and/or psychologists. Recommendations for clinical decisions are provided.